Sosialisasi Strategi Pengembangan Kesiapan Sekolah Siswa TK di Masa Kurikulum Merdeka Belajar - Asti B. Adwitiya; Anggraeni Swastika Sari; Nanda Gea Sabrinna; Vito Noer Dianratno (Indonesian Journal Publisher, 2024)
Quality education is one aspect of the Sustainable Development Goals (SDGs) that needs to be considered from the early childhood education level. Early childhood school readiness will greatly determine the academic achievement of students at the primary school level. Therefore, to achieve quality education for children, synergy is needed from teachers and parents in encouraging kindergarten B students' school readiness to be optimal in participating in education at the elementary level. This service program was carried out to answer these challenges. This program is a follow-up to research on kindergarten B children's school readiness. Based on the results of the school readiness assessment in the previous research, a socialization was held related to the profile of children's school readiness along with strategies that can be done by teachers and parents in optimizing children's school readiness. This socialization was attended by teachers and parents of TK X in Jember Regency. A total of 44 participants had their satisfaction level measured to ensure that there were benefits gained from this program. In general, the participants of this socialization had high satisfaction (65%), while some others expressed a low level of satisfaction (35%). This socialization is expected to help teachers and parents work together to provide quality education for children according to their children's readiness.